Using Sequences Pictures to Increase Middle-School Students' Ability in Narrative Text - Amilah, Amilah (ETDC: Indonesian Journal of Research and Educational Review, 2024)
The objectives of the research are to describe the improvement of students’ ability in writing narrative text through sequence pictures as a learning media. This research focuses on two problem statements: how does the use of sequence pictures as a learning medium enhance students' ability to write narrative texts? What is the reaction of the third-year students at Public Middle School 1 Sampaga to the use of sequence pictures as a learning medium? The study also seeks to understand the students' reactions to the use of sequence pictures as a learning tool. The researcher conducted a classroom action research study that consists of two cycles. The research findings revealed that the students' proficiency in narrative writing remained low. The students’ class mean score in the pre-cycle is 43.24. After giving sequence pictures as a learning media in the first cycle, the class mean score improved to 59.68. Then, in the second cycle, the class mean score improved to 76.96. It could be concluded that the third-year students at Public Middle School 1 Sampaga, especially in class IX D, have a skill to make excellent content, organization, and vocabulary using writing narrative text after applying sequence pictures as a teaching media.